Loyalty and neglect as responses to dissatisfying job conditions (the role of personality) / Ismi Rajiani and Edna Buyong - Rajiani, Ismi; Buyong, Edna (Universiti Teknologi MARA, Shah Alam, 2013)
This study clarifies the role of personality trait when reacting to dissatisfying job conditions by applying Hirschman’s exit, voice, loyalty, and Rosbult’s neglect as employees’ response within Malaysian public sector employees. Structural equation modeling is used to fit the data provided by 150 public sector employees working in various government agencies. Due to the specific organizational culture, this study argues that employees in public sector will choose response either loyalty or neglect depending on which personality traits they belong to. Drawing on the Five Factor Model (FFM), the study finds out that Openness to Experience, Conscientiousness and Extraversion when something unfavorable happens in an organization, they will remain in organization but exhibit passive withdrawal behaviors such as reporting sick, coming in late, putting less effort, putting not enough effort into their work, and missing out on meetings (neglect) while Agreeableness and Emotional Stability will remain confident, assume that in the end everything will work out fine and finally wait and hope for improvement (loyalty).